Clinical presentation of cystic fibrosis at the time of diagnosis: a multicenter study in a region without newborn screening - Fatemeh FARAHMAND; Manijeh KHALILI; Leila SHAHBAZNEJAD; Armin HIRBOD-MOBARAKEH; Mehri NAJAFI SANI; Ahmad KHODADAD; Farzaneh MOTAMED; Nima REZAEI (Turkish Journal of Gastroenterology, 2019)
-